Resistance of titanium alloys to cavitation wear - Klimenko, І.О.; Marinin, V.G.; Ovcharenko, V.D.; Kovalenko, V.I.; Kuprin, A.S.; Reshetnyak, O.M.; Belous, V.A.; Rostova, H.Yu. (Вопросы атомной науки и техники, 2022)
The wear rate of titanium alloys VT1-0, TC5, VT6, VT14, OT4 under the action of microshocks due to cavitation, which is created in distilled water under the surface of the ultrasonic wave emitter, were determined. It was found that the increase in hardness and improvement of cavitation wear resistancefor these alloys depends on the alloying elements, and is also increased after heat treatment and ion-plasma modification of the sample surface. Although no unambiguous correlation was found between the structural class of the alloys and their cavitation wear. Due to ion-plasma modification of alloys, the cavitation wear resistanceis increased by several times, in particular, the VT6 alloy by 3 times. The phase composition of the samples before and after ion-plasma modification was studied and it was found that alloy resistance to cavitation significantly depends on it. Визначена швидкість зношування титанових сплавів ВТ1-0, ТС5, ВТ6, ВТ14, ОТ4 під дією мікроударів у результаті дії кавітації, яка створюється в дистильованій воді під поверхнею випромінювача ультразвукових хвиль. Встановлено, що підвищення твердості та покращення кавітаційної стійкості для цих сплавів залежать від легуючих елементів, а також збільшуються після термічної обробки та іонно-плазмової модифікації поверхні зразка. Однозначної кореляції між структурним класом сплавів та кавітаційним зносом не виявлено. Внаслідок іонно-плазмової модифікації сплавів стійкість до кавітаційного зносу збільшується в кілька разів, зокрема сплаву ВТ6 у 3 рази. Досліджено фазовий склад зразків до і після іонно-плазмової модифікації та встановлено, що від нього суттєво залежить стійкість сплаву до кавітації. Определена скорость износа титановых сплавов ВТ1-0, ТС5, ВТ6, ВТ14, ОТ4 под действием микроударов в результате действия кавитации, которая создается в дистиллированной воде под поверхностью излучателя ультразвуковых волн. Установлено, что повышение твердости и улучшение кавитационной устойчивости для этих сплавов зависят от легирующих элементов, а также увеличиваются после термической обработки и ионно-плазменной модификации поверхности образца. Однозначной корреляции между структурным классом сплавов и кавитационным износом не обнаружено. Вследствие ионно-плазменной модификации сплавов стойкость к кавитационному износу увеличивается в несколько раз, в частности сплава ВТ6 в 3 раза. Исследован фазовый состав образцов до и после ионно-плазменной модификации и установлено, что от него существенно зависит стойкость сплава к воздействию кавитации.